Eastern Europe phrasebook & dictionary - Myers, Jenna (Lonely Planet, 2019)
Lonely Planet's Eastern Europe Phrasebook is your passport to culturally enriching travels with the most useful European phrases and vocabulary for all your travel needs. Ask for directions to historic sites, order regional delicacies, and propose a toast like a local- all with your trusted travel companion.